The death penalty and race and how the ultimate punishment highlights the flaws in our criminal justice system - Williams, Kenneth (Revista Direitos Fundamentais e Alteridade, 2022)
The United States often likes to portray it’s criminal justice system as a model for the rest of the world. In the U.S. an individual accused of a crime has numerous constitutional and other protections. Defendants in the United States are presumed innocent. They have a right to be represented at trial by a lawyer even if they cannot afford one. Defendants have the right to confront their accusers face to face. If the state is in possession of exculpatory evidence, the prosecutor has a constitutional duty to disclose this evidence. Defendants also cannot languish in prison for long periods of time as they have the right to a speedy and public trial. Finally, defendants have the right to have the case tried before a jury of their peers and an impartial judge. Unfortunately for many defendants these rights are merely theoretical. For many defendants who are poor, minority and otherwise disadvantaged, these rights are not fully realized. Nowhere is this more evident than with the death penalty. In this article, I will discuss the capital punishment system in the United States, a system which highlights some of the systemic problems that plague the U.S. criminal justice system.